AN OUTCOME OF CONSERVATIVE MANAGEMENT OF PRIMARY NOCTURNAL ENURESIS IN CHILDREN - Shah, Syed Sajid Hussain; Bibi Aalia; Ali Raza; Shahzad Najeeb; Anis-ur-Rehman (Journal of Ayub Medical College Abbottabad, 2021)
Background: Primary nocturnal enuresis is one of the common problems in children. Mostly parents are concern for this condition in children and also children are depressive from this condition. The main stay of treatment is the training of child. The objective of this study was to look for the outcome of conservative management of primary nocturnal enuresis. Methods: This study was done in OPD of paediatrics department. Patients aged five year or more were included in the study. Patient age, weight, sex, blood pressure, family history in siblings and parents, number of wet days/week, recorded on specific proforma along with renal function tests. Patients were advised fluid restriction after evening and micturition before sleep and after 2-3 hours of sleep. Follow up was done after six months to observe for the impact of habit change. Data has been analysed by SPSS 20 and results are taken significant with p-value <0.05. Results: Out of 81 patients, 41 were male and 40 females. Age ranged from 5 to 14 years and mean age was 8.2±2.35 years. There were 11.1% parents who had primary nocturnal enuresis during childhood and in 29.6% siblings, history was positive. Follow up at 6 months, 58% patients improved while 42% showed no improvement. There was significant relationship between evening fluid restriction, micturition before and after sleep with improvement at 6 months with p-value of 0.010, <0.001 and 0.002 respectively. Conclusion: Conservative management is the effective intervention in children as parents should be emphasized for habit change. Keywords: Primary nocturnal enuresis; Children; Conservative management